Effect of Sporulation Medium on Wet-Heat Resistance and Structure of Alicyclobacillus Acidoterrestris Dsm 3922-Type Strain Spores and Modeling of the Inactivation Kinetics in Apple Juice - Molva, Çelenk; Baysal, Ayşe Handan; Baysal, Ayşe Handan; Molva, Çelenk (Elsevier Ltd., 2014)
Alicyclobacillus acidoterrestris is a spoilage bacterium in fruit juices leading to high economic losses. The present study evaluated the effect of sporulation medium on the thermal inactivation kinetics of A. acidoterrestris DSM 3922 spores in apple juice (pH3.82±0.01; 11.3±0.1 °Brix). Bacillus acidocaldarius agar (BAA), Bacillus acidoterrestris agar (BATA), malt extract agar (MEA), potato dextrose agar (PDA) and B. acidoterrestris broth (BATB) were used for sporulation. Inactivation kinetic parameters at 85, 87.5 and 90°C were obtained using the log-linear model. The decimal reduction times at 85°C (D85°C) were 41.7, 57.6, 76.8, 76.8 and 67.2min; D87.5°C-values were 22.4, 26.7, 32.9, 31.5, and 32.9min; and D90°C-values were 11.6, 9.9, 14.7, 11.9 and 14.1min for spores produced on PDA, MEA, BATA, BAA and BATB, respectively. The estimated z-values were 9.05, 6.60, 6.96, 6.15, and 7.46, respectively. The present study suggests that the sporulation medium affects the wet-heat resistance of A. acidoterrestris DSM 3922 spores. Also, the dipicolinic acid content (DPA) was found highest in heat resistant spores formed on mineral containing media. After wet-heat treatment, loss of internal volume due to the release of DPA from spore core was observed by scanning electron microscopy. Since, there is no standardized media for the sporulation of A. acidoterrestris, the results obtained from this study might be useful to determine and compare the thermal resistance characteristics of A. acidoterrestris spores in fruit juices. © 2014 Elsevier B.V.
Keywords: Dipicolinic acid content; Fruit juices; Inactivation; Spoilage; Sporulation media